2019
DOI: 10.3389/fphar.2019.01423
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Interaction Profiles of 4-Alkoxy-Substituted 2,5-Dimethoxyphenethylamines and Related Amphetamines

Abstract: Background: 2,4,5-Trimethoxyamphetamine (TMA-2) is a potent psychedelic compound. Structurally related 4-alkyloxy-substituted 2,5-dimethoxyamphetamines and phenethylamine congeners (2C-O derivatives) have been described but their pharmacology is mostly undefined. Therefore, we examined receptor binding and activation profiles of these derivatives at monoamine receptors and transporters. Methods: Receptor binding affinities were determined at the serotonergic 5-HT1A, 5-HT2A, and 5-HT2C receptors, trace amine-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 49 publications
6
27
0
Order By: Relevance
“…Consistent with the in vitro findings, psychedelic phenethylamines were shown to induce 5-HT 2A -dependent behaviors in vivo, such as wet dog shakes, back muscle contractions, and a head twitch response (Elmore et al 2018;Fantegrossi et al 2005;Halberstadt et al 2020;Halberstadt and Geyer 2014). In addition to interactions with serotonergic receptors, phenethylamine psychedelics have been shown to interact with other monoaminergic targets, including adrenergic, dopaminergic, and histaminergic receptors, monoamine transporters, and MAOs (Eshleman et al 2018;Kolaczynska et al 2019;Luethi et al 2018d;Noble et al 2018;Rickli et al 2015c;Wagmann et al 2019a). However, most of these interactions are weak compared with the potent interactions with serotonergic receptors.…”
Section: Mechanism Of Action Of Phenethylaminesmentioning
confidence: 63%
See 3 more Smart Citations
“…Consistent with the in vitro findings, psychedelic phenethylamines were shown to induce 5-HT 2A -dependent behaviors in vivo, such as wet dog shakes, back muscle contractions, and a head twitch response (Elmore et al 2018;Fantegrossi et al 2005;Halberstadt et al 2020;Halberstadt and Geyer 2014). In addition to interactions with serotonergic receptors, phenethylamine psychedelics have been shown to interact with other monoaminergic targets, including adrenergic, dopaminergic, and histaminergic receptors, monoamine transporters, and MAOs (Eshleman et al 2018;Kolaczynska et al 2019;Luethi et al 2018d;Noble et al 2018;Rickli et al 2015c;Wagmann et al 2019a). However, most of these interactions are weak compared with the potent interactions with serotonergic receptors.…”
Section: Mechanism Of Action Of Phenethylaminesmentioning
confidence: 63%
“…At 5-HT 2A receptors, 2C and NBOMe derivatives were shown to be partial or full agonists, depending on the functional in vitro assay (Eshleman et al 2014(Eshleman et al , 2018Jensen et al 2017;Kolaczynska et al 2019;Luethi et al 2018dLuethi et al , 2019cMoya et al 2007;Rickli et al 2015c). NBOMe derivatives and most 2C derivatives have been shown to be partial agonists at 5-HT 2B receptors (Eshleman et al 2018;Jensen et al 2017;Kolaczynska et al 2019;Luethi et al 2018d;Rickli et al 2015c). At 5-HT 2C receptors, 2C derivatives were shown to be partial or full agonists (Eshleman et al 2014;Moya et al 2007), and NBOMe derivatives were shown to be full agonists (Eshleman et al 2018;Jensen et al 2017).…”
Section: Mechanism Of Action Of Phenethylaminesmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenethylamine derivatives interact mainly with cortical serotonin receptors, with the highest affinity for 5-HT2A receptors. 136 NBOMe derivatives have higher affinity for 5-HT2A and 5-HT2C receptors and lower affinity for 5-HT1A receptors compared with their 2C analogues. Tryptamine derivatives have an affinity for 5-HT1A, 5-HT2A and 5-HT2C receptors, and can inhibit reuptake and increase the release of serotonin.…”
Section: Synthetic Hallucinogensmentioning
confidence: 93%